Exploring cultural factors and coping strategies used by Malaysian female working adults with social anxiety disorder (SAD) - Nur Helena Ng Yusof Ng,; Nur Aini Alegrea Suner, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Employees actively pursue career progression, yet social anxiety disorder (SAD) may have impeded workplace performance for promotional opportunities. Nonetheless, SAD particularly affects female employees, and is more prevalent in individualistic countries, albeit those from collectivistic countries experienced more symptoms. The present study aims to explore the cultural factors contributing to the development of SAD and to identify the coping strategies used by Malaysian female working adults with SAD to manage their symptoms. Semi structured interviews with a total of 14 questions were conducted as a part of qualitative research with 4 participants who had at least one year of working experience, been diagnosed with SAD, were able to converse well in English, and had no comorbidity with Schizoaffective disorder. The participants were recruited through purposive and snowball sampling, and information obtained about their experiences was thematically analysed (TA). The findings revealed cultural factors such as power distance, norms, attitude, collectivism, belief, family system, and self-concept, as well as coping strategies such as maladaptive, emotion-focused, and problem-focused. Overall, this study sheds light on the cultural factors that influence the development of SAD among employees, and the coping strategies that can alleviate the associated symptoms in both general and workplace settings.